Influence of Opportunity to Learn Indices and Education Status on Students' Mathematics Achievement Growth. (May 2017) - Elliott, Stephen N.; Kurz, Alexander; Tindal, Gerald; Yel, Nedim
We examined instructional processes in classrooms where students with and without disabilities received mathematics instruction to understand the relationship among key instructional process variables and achievement as measured by interim and end-of-year summative assessments. Teachers ( N = 78) completed instructional logs daily and administered easyCBM probes quarterly to 162 students with disabilities and 165 students without disabilities. Examination of instructional data indicated both groups of students had nearly equal opportunities to learn (OTLs) the same mathematics content, yet there were significant differences in these students' mathematics achievement on interim and summative tests. Special education status and instructional practices were found to be significant predictors of achievement growth. Furthermore, grade level and special education status, along with OTL scores, accounted for significant variance in end-of-year mathematics scores. Discussion of results focuses on instructional practice implications and the role these practices play in achievement gaps.